1967
DOI: 10.1071/ar9670495
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay responses of ewes to legume swards. II. Uterine weight results from swards

Abstract: Three years' results of sheep uterine weight bioassays on a range of clover swards are presented. Trifolium pratense L. (var. Grasslands Hamua Broad) and Trifolium subterraneum L. (var. Dinninup, Dwalganup, Tallarook, and Yarloop) showed high activity whenever they were green. Trifolium fragiferum L. (mixed+Palestine), Trifolium repens L. (var. Victorian Irrigation), and Trifolium subterraneum L. (var. Bacchus Marsh, Howard, Marrar, and a breeder's selection) showed variable activity; Medicago sativa L. (var. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Pasture containing~1000 mg/kg will inhibit oestrus and ovulation [24] but pasture containing 200-400 mg/kg will only depress ovulation [27]. Smith et al (1980) [140] reported that a coumestrol concentration of 25 mg/kg DM was sufficient to suppress the ovulation rate of ewes, a claim supported by earlier work [22,141].…”
Section: Tolerance Levelssupporting
confidence: 57%
“…Pasture containing~1000 mg/kg will inhibit oestrus and ovulation [24] but pasture containing 200-400 mg/kg will only depress ovulation [27]. Smith et al (1980) [140] reported that a coumestrol concentration of 25 mg/kg DM was sufficient to suppress the ovulation rate of ewes, a claim supported by earlier work [22,141].…”
Section: Tolerance Levelssupporting
confidence: 57%
“…However, there is no pattern in isoflavone distribution, either as single compounds or total contents among the different plant parts (Cook et al, 1995;Vetter, 1995;Wu et al, 2003;Table 4). There are some large differences between cultivars (Bennet et al, 1967;Carlsen et al, 2008;Sachse, 1974), while some show no differences (Saloniemi et al, 1993). The formononetin content can differ between resistant and susceptible populations (Cook et al, 1995).…”
Section: Isoflavones/isoflavanones In White Clovermentioning
confidence: 99%
“…Many isoflavones show antifungal properties (Ingham, 1982;Van Etten, 1976;Virtanen and Hietala, 1958;Weidenbçrner et al, 1990) and estrogenic effects in ruminants (Bennet et al, 1967;Pettersson et al, 1984;Saloniemi et al, 1993;Shutt and Braden, 1968;Shutt and Cox, 1972). The isoflavones formononetin and biochanin A stimulate colonization by one AM fungus (Glomus intraradices) and white clover growth (Siqueira et al, 1991a), while biochanin A inhibit the growth of another AM fungus (Gigaspora margarita) (BØcard et al, 1992).…”
Section: Biological Effects Of Isoflavones and Isoflavanones And Theimentioning
confidence: 99%
“…1964).· However, oestrogenic effects of this clover in sheep and cattle have occasionally been reported in the U.S.A. (Sanger and Bell 1961;Wright 1960), Japan (Ochi et at. 1964), Australia (Bennett et at. 1967), andBritain (Newton et at.…”
Section: Introductionmentioning
confidence: 99%